Analisis Kesalahan Morfologi Arab pada Lembar Jawaban Siswa Madrasah Aliyah - Zuhriyah, Arina Alfi Aminatuz; Mukani, Samsul; Wijayanti, Lisma Meilia (Institut Agama Islam Sunan Giri Ponorogo, 2022)
The focus of this research is to describe the analysis of morphological language errors in the answer sheets of class XI MIP MA Ma'arif Al Falah Sawoo Ponorogo students' answer sheets. The data is divided into two, namely primary data and secondary data. Primary data was obtained from the writing of self-answer sheets for class XI MIP MA Ma'arif Al Falah Sawoo Ponorogo. Meanwhile, secondary data was obtained from supporting research literature, either printed or online. Data collection techniques were carried out by observation, interviews, and documentation. Data analysis used the theory of Milles and Huberman, with data reduction steps, data presentation, and concluding. The results showed that the students of class XI MIPA MA Maarif Al Falah Sawoo had not yet mastered the science of short in word-formation according to the context requested. This is evidenced by the many mistakes in word formation and wrong layout in the preparation of perfect sentences.